An economic geography of global finance: ownership concentration and stock-price volatility in German firms and regions. - Clark, G; Wójcik, D (Routledge, 2003)
For some, global finance is ubiquitous. The growth of advanced electronic communications combined with computer-driven, top-down investment strategies has provided institutional investors access to the most sheltered capital markets, including those of continental Europe. By contrast, many economic geographers find this view of the world both simplistic with respect to the persistence of different nation-state regulatory traditions and highly misleading as to the most effective way of generating long-term value for investors and communities. In this article, we provide evidence to support these claims, concentrating upon the relationship between systems of corporate governance and stock-price volatility. The geography of market information is our point of departure, illustrated by reference to the informational content of stock market prices for two German companies, Mannesmann (now Vodafone) and Bayerische Motorenwerke (BMW), representatives of rather different regional models of capital accumulation. More systematically, we report the results of statistical analyses of the volatility of daily stock-market prices for German DAX30 and DAX100 firms, arguing that their apparent characteristics have important lessons for the value and significance of bottom-up portfolio investment strategies. These results, combined with case studies of the two German firms, are used to suggest that the geography of finance remains a vital component of global investment strategies, an argument that has important implications for academic analysis inside and outside of geography.